A fluorescence in situ hybridization method for the measurement of denitrifying phosphorus-accumulation organisms and study on the metabolisms of activated sludge. (20th May 2017) - Lu, Qian; Qian, Wei; Liu, Wen; Liu, Hui; Zhou, Wenguang; Deng, Jinchuan; Wang, Qin; Sun, Yanfu; Zhou, Kangqun; Ming, Caibing; Wang, Baoe; Yao, Chuang; et al.
Abstract: A new method using polyphosphate kinase (PPK) probe was developed in this study to measure the ratio of denitrifying phosphate-accumulating organisms (DNPAOs) to bacteria. Advantages and disadvantages of this method and previously published methods were evaluated. Biochemical characteristics and metabolic mechanisms of the bacterial community in activated sludge were analyzed. The result indicated that PPK probe targeting at the gene of polyphosphate kinase in bacterial cells could marked more PAOs than traditional PAO probes. The ratio of DNPAOs/bacteria reached 60.30% in activated sludge. The whole bacterial community in activated sludge, at the end of A/A stage, presented significant non-fermentative characteristics although the activated sludge still contained some fermentative bacteria. Study on the metabolic mechanisms suggested that intracellular PHB served as the major carbon source and energy source of bacterial community in activated sludge.